An update on the Tibetan argali Ovis ammon hodgsoni in Nepal - Kusi, N; Acharya, R; Ghimirey, Y; Adhikary, B; Werhahn, G (De Gruyter, 2018)
In Nepal, the Tibetan argali Ovis ammon hodgsoni was documented from the Mustang and Humla districts until 2013. In 2016, we observed a young ram in the Dolpa district, providing the third locality record. We compiled historical data and our own observation data from 2013 to 2016 to discuss the present distribution of the Tibetan argali in Nepal. We suggest reassessing the National Red List to reclassify it as either "endangered" or "vulnerable". We recommend management of livestock numbers, promotion of traditional practice of rotational grazing and raising conservation awareness, especially among herders visiting the argali habitat, for long-term conservation of the species in Nepal.